2021
DOI: 10.1186/s12870-021-03184-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of OSCA gene family members in Vigna radiata and their involvement in the osmotic response

Abstract: Background Mung bean (Vigna radiata) is a warm-season legume crop and belongs to the papilionoid subfamily of the Fabaceae family. China is the leading producer of mung bean in the world. Mung bean has significant economic and health benefits and is a promising species with broad adaptation ability and high tolerance to environmental stresses. OSCA (hyperosmolality-gated calcium-permeable channel) gene family members play an important role in the modulation of hypertonic stress, such as drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 48 publications
4
29
0
Order By: Relevance
“…Current research suggests that OSCA family members act as osmotic sensors to mediate the increase in intracellular Ca 2+ concentration induced by hyperosmolality and control the closure of stomata in the process of immune signal transduction [ 15 , 25 ]. In view of the importance of the functions of OSCA family members, they have been systematically identified in several species, including A. thaliana , rice, maize, and Vigna radiata (L.) [ 15 , 16 , 17 , 18 ] but not so far in wheat. In this study, 42 OSCA members were identified using T. aestivum genomic data, and the expression patterns of 15 members in different tissues and under three abiotic stress treatments were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Current research suggests that OSCA family members act as osmotic sensors to mediate the increase in intracellular Ca 2+ concentration induced by hyperosmolality and control the closure of stomata in the process of immune signal transduction [ 15 , 25 ]. In view of the importance of the functions of OSCA family members, they have been systematically identified in several species, including A. thaliana , rice, maize, and Vigna radiata (L.) [ 15 , 16 , 17 , 18 ] but not so far in wheat. In this study, 42 OSCA members were identified using T. aestivum genomic data, and the expression patterns of 15 members in different tissues and under three abiotic stress treatments were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The number of OSCAs in the T. aestivum genome is more than that of A. thaliana , rice, maize, and Vigna radiate [ 15 , 16 , 17 , 18 ], perhaps in part because the T. aestivum genome is larger. Phylogenetic analysis showed that TaOSCAs fall into four clades ( Figure 1 ), consistent with the topology of the phylogenetic tree of A. thaliana OSCA members [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations